History of the Development of the School Education System in the Republic of Kazakhstan - Karabota, B.Sh.; Aldabergenova, M.K. (Karagandy University of the name of acad. E.A. Buketov, 2025)
Most modern countries have recognized the need to modernize general secondary education as one of the priority goals of national education reform, since the effectiveness of general education schools is an important indicator of a country’s level of development and its socio-economic potential. In this regard, the experience of modernizing general secondary education in the Republic of Kazakhstan is of particular interest at present, where a large-scale reform of the entire education system is being carried out, corresponding to fundamental changes in all spheres of the economy and public life. General secondary education plays a key role in addressing this problem, and its modernization is a priority of national education reform. The article examines the processes of school education reform in the Republic of Kazakhstan and highlights the stages of fundamental changes in the field of education. The authors summarize the results of each stage of school education reform, highlight positive results, identify problems, national characteristics, and the relationship between the general and the specific, between global trends and national specifics. The authors of this article examine the process of reforming general secondary education in Kazakhstan and describe the concepts and programs for modernizing general secondary education.
Keywords: modernization programs; modernization of school education; stages of school education reform; general education school; history of the school education system